A high-coverage artificial chromosome library for the genome-wide screening of drug-resistance genes in malaria parasites - Iwanaga, Shiroh; Kaneko, Izumi; Yuda, Masao (Genome Research, 2012)
The global spread of drug-resistant parasites is a serious problem for the treatment of malaria. Although identifying drug-resistance genes is crucial for the efforts against resistant parasites, an effective approach has not yet been developed. Here, we report a robust method for identifying resistance genes from parasites by using a Plasmodium artificial chromosome (PAC). Large genomic DNA fragments (10–50 kb) from the drug-resistant rodent malaria parasite Plasmodium berghei were ligated into the PAC and directly introduced into the drug-sensitive (i.e., wild-type) parasite by electroporation, resulting in a PAC library that encompassed the whole genomic sequence of the parasite. Subsequently, the transformed parasites that acquired resistance were selected by screening with the drug, and the resistance gene in the PAC was successfully identified. Furthermore, the drug-resistance gene was identified from a PAC library that was made from the pyrimethamine-resistant parasite Plasmodium chabaudi, further demonstrating the utility of our method. This method will promote the identification of resistance genes and contribute to the global fight against drug-resistant parasites.